Rancang Bangun Aplikasi Kasir Berbasis Web pada Usaha Roti Karkus - Siregar, Lidya Rizky (UNIVERSITAS KALBIS, 2025)
The purpose of this research is to build a website-based cashier application for the Roti Karkus Business. This application can record sales transactions and display sales reports per day and per month. This application is built using programming languages such as HTML, CSS, PHP and JavaScript and MySQL as the database. The software development method used in building this application is the Rational Unified Process (RUP) with the Unified Modeling Language (UML) modeling. This application is built in four phases, namely the inception phase, the elaboration phase, the construction phase and the transition phase. This web-based cashier application was tested using the Black Box and User Acceptance Test (UAT) methods. The results of this study are a website-based cashier application that can be accessed by employees and owners of the Roti Karkus Business via a laptop or smart phone connected to the internet.